The Mediating Role of Employee Loyalty between Employee Empowerment and Employee Innovative Behavior: A Study from Teknopark Istanbul - (:unkn) unknown (My University, 2018)
This study investigates the mediating role of employee loyalty on the relationship between employee empowerment and employee innovative behavior. According to literature review, there is a dearth of studies investigating employee empowerment, employee loyalty and its effect on employee innovative behavior. Thus, this study will fill in the gap in the literature. There are two reasons why Teknopark Istanbul is selected for the research. First, Technopark is a new sector in Turkey, and there is a scarce of studies related to the firms operating within technoparks. Second, the firms operating in technoparks have mainly entrepreneurial, technological and innovative nature. In this study, data were collected from 219 employees in technology firms within Teknopark Istanbul, Turkey. The findings of this study indicate that employee loyalty has a mediating role on the relationship between employee empowerment and employee innovative behavior.
Keywords: Tarih